ARIA digital anamorphosis - Bousquet, Jean (2021)
Funding: MA reports personal fees from POCI-01-0145-FEDER-029130 mINSPIRERS—mHealth to measure and improve adherence to medication in chronic obstructive respiratory diseases—generalization and evaluation of gamification, peer support and advanced image processing technologies from ERDF (European Regional Development Fund) funded by the COMPETE2020 and by National Funds through FCT (Fundação para a Ciência e a Tecnologia)…